Alternative disease management strategies for organic apple production in the United Kingdom - Lucas Alexander Shuttleworth (CABI Agriculture and Bioscience)
Abstract Apple is a globally important tree fruit. In the United Kingdom (UK) and mainland Europe, there is ongoing consumer and environmental concern regarding over-reliance on conventional chemicals for disease control. This has resulted in an increase in withdrawal of active ingredients and legal use restrictions over recent years. The loss of active ingredients can be problematic for growers, who have relied on the generally more predictable and efficacious management that results from using conventional chemicals. Organic disease management methods are generally more sustainable over the long term as organic methods have fewer negative impacts on the environment and on human health. Key diseases of organic UK apple production include scab, European canker, powdery mildew, apple replant disease, and brown rot/blossom wilt. The recommended organic control measures depend on the disease. Measures range from the use of host resistance, rootstock and scion cultivar selection, planting location of trees, application of biological control agents, soil amendments, cultural management, postharvest treatments, disease modelling and forecasting. The challenge when using organic methods is results are often more variable and less predictable than when using conventional chemicals. Biological control agents, for example, often require more applications than chemicals, need correct timing to work effectively, and can be sensitive to weather and orchard management. Additionally, a thorough understanding of disease ecology by growers is helpful for more effective implementation of organic control methods. Invasive pathogens not currently present in the UK that may affect apple production including Xylella fastidiosa and Valsa mali, and the potential effects of climate change on pathogens already present such as Erwinia amylovora (fireblight) are discussed. The consequences of climate change are difficult to predict due to the changeable nature of the weather and the variation in factors contributing to climate change. However, a warming planet and more unpredictable weather patterns may favour range expansion of pathogens, while increasing plant stress and susceptibility. This review presents various methods that can be applied as alternatives to conventional chemicals for disease control in organic apple production to provide economic efficiency, environmental sustainability, and the supply of safe nutritious food.